Cefiderocol treatment for carbapenem-resistant Acinetobacter baumannii infection in the ICU during the COVID-19 pandemic: a multicentre cohort study. Issue 4 (17th November 2021) - Pascale, Renato; Pasquini, Zeno; Bartoletti, Michele; Caiazzo, Luca; Fornaro, Giacomo; Bussini, Linda; Volpato, Francesca; Marchionni, Elisa; Rinaldi, Matteo; Trapani, Filippo; Temperoni, Chiara; Gaibani, Paolo; et al.
Abstract: Objectives: To analyse the impact of cefiderocol use on outcome in patients admitted to the ICU for severe COVID-19 and further diagnosed with carbapenem-resistant Acinetobacter baumannii (CR-Ab) infection. Methods: Retrospective multicentre observational study was performed at four Italian hospitals, from January 2020 to April 2021. Adult patients admitted to ICU for severe COVID-19 and further diagnosed with CR-Ab infections were enrolled. Patients treated with cefiderocol, as compassionate use, for at least 72 h were compared with those receiving alternative regimens. Primary endpoint was all-cause 28 day mortality. The impact of cefiderocol on mortality was evaluated by multivariable Cox regression model. Results: In total, 107 patients were enrolled (76% male, median age 65 years). The median time from ICU admission to CR-Ab infection diagnosis was 14 (IQR 8–20) days, and the main types of CR-Ab infections were bloodstream infection (58%) and lower respiratory tract infection (41%). Cefiderocol was administered to 42 patients within a median of 2 (IQR 1–4) days after CR-Ab infection diagnosis and as monotherapy in all cases. The remaining patients received colistin, mostly (82%) administered as combination therapy. All-cause 28 day mortality rate was 57%, without differences between groups (cefiderocol 55% versus colistin 58% P = 0.70). In multivariable analysis, the independent risk factor for mortality was SOFA score (HR 1.24, 95% CI 1.15–1.38, P < 0.001). Cefiderocol was associated with a non-significant lower mortality risk (HR 0.64, 95% CI 0.38–1.08, P = 0.10). Conclusions: Our study confirms the potential role of cefiderocol in the treatment of CR-Ab infection, but larger clinical studies are needed.